2022
DOI: 10.15585/mmwr.mm7105e1
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection and Hospitalization Among Adults Aged ≥18 Years, by Vaccination Status, Before and During SARS-CoV-2 B.1.1.529 (Omicron) Variant Predominance — Los Angeles County, California, November 7, 2021–January 8, 2022

Abstract: On February 1, 2022, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).COVID-19 vaccines are effective at preventing infection with SARS-CoV-2, the virus that causes COVID-19, as well as severe COVID-19-associated outcomes in real-world conditions (1,2). The risks for SARS-CoV-2 infection and COVID-19-associated hospitalization are lower among fully vaccinated than among unvaccinated persons; this reduction is even more pronounced among those who have received addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
91
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 6 publications
13
91
0
1
Order By: Relevance
“…A previous study also found that, compared with the period of Delta predominance, the period of Omicron predominance in Los Angeles County was associated with a decrease in the degree of protection against COVID-19 and hospitalization (6). Despite this, COVID-19 vaccination, including a booster dose, was associated with lower likelihood of ICU admission during the Omicron period, and lower likelihood of death among adults aged ≥65 years, who are at higher risk for severe outcomes when hospitalized with COVID-19 (7,8).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A previous study also found that, compared with the period of Delta predominance, the period of Omicron predominance in Los Angeles County was associated with a decrease in the degree of protection against COVID-19 and hospitalization (6). Despite this, COVID-19 vaccination, including a booster dose, was associated with lower likelihood of ICU admission during the Omicron period, and lower likelihood of death among adults aged ≥65 years, who are at higher risk for severe outcomes when hospitalized with COVID-19 (7,8).…”
Section: Discussionmentioning
confidence: 92%
“…First, sequencing data were not available to identify the SARS-CoV-2 variant. However, based on California genomic surveillance data, which is based on sequencing of ≥10% of all positive RT-PCR tests in the state, ¶ ¶ ¶ and on recent genomic surveillance for Los Angeles County (7), the Delta and Omicron variants accounted for the majority of sequenced isolates throughout their respective predominance periods. Second, the proportion of Omicron-period hospitalizations attributed to COVID-19 could not be compared with earlier periods, so it is unclear whether the proportion represented a change from an earlier period.…”
Section: Figure Intensive Care Unit Admission Use Of Invasive Mechani...mentioning
confidence: 99%
“…When the Delta variant was the predominant strain in the United States, hospitalization rates were 12.9 times higher in those who were not vaccinated. Similarly, hospitalization rates were 5.3 times higher in the unvaccinated group when the Omicron variant was dominant 135 . These are reflected in clinical studies where two doses of the BNT162b2 vaccine have an efficacy against hospital admission of 70% and 93% for the Omicron and Delta variants, respectively 136 .…”
Section: Strategies Against the Omicron Variantmentioning
confidence: 88%
“…Similarly, hospitalization rates were 5.3 times higher in the unvaccinated group when the Omicron variant was dominant. 135 These are reflected in clinical studies where two doses of the BNT162b2 vaccine have an efficacy against hospital admission of 70% and 93% for the Omicron and Delta variants, respectively. 136 Similarly, another research from the UK illustrated that without being vaccinated before Omicron infection, the hospitalization rate was 0.76.…”
Section: Strategies Against the Omicron Variantmentioning
confidence: 99%
“…The 3 rd mRNA vaccine dose produces an initial increase in circulating anti-Omicron neutralizing antibodies, but titers remain 10-20-fold lower than against Wuhan-Hu-1 and are, in many cases, insufficient to prevent infection 7 . Despite the reduced protection from infection, individuals that received 3 doses of an mRNA vaccine were highly protected from the more serious consequences of infection 8 . Here we examine the memory B cell repertoire in a longitudinal cohort of individuals receiving 3 mRNA vaccine doses 9,10 .…”
mentioning
confidence: 99%